Resilience as a Preventive Factor in Early Childhood Psychosis - Hendy Yogya (Scientia Psychiatrica, 2021)
Resilience is a person's ability to survive, rise, and adapt to difficult conditions. Individuals who have resilience are able to quickly return to their pre-psychic trauma, appear immune from negative life events, and are able to adapt to extreme stress and suffering. A child with disabilities, from an early age, the parents have to "prepare the child" from various aspects, such as physical, mental and social in facing the life that will be faced. So that children are better prepared to face challenges and do not suffer from a serious mental disorder even genetically they have the potential for psychiatric disorders, but with preparation and training in resilience from an early age and develop positive potentials of children and generate mature coping mechanisms, children will be better prepared to face life (Psychological Readiness) towards welfare and prosperity (Wellbeing) in society. This literature review aims to discuss resilience as a protective factor in early childhood psychosis.